Graphene oxide-induced formation of a boron-doped iron oxide shell on the surface of NZVI for enhancing nitrate removal. (August 2020) - Han, Luchao; Li, Bengang; Tao, Shu; An, Jie; Fu, Bo; Han, Yunman; Li, Wei; Li, Xinyue; Peng, Siyuan; Yin, Tianya
Abstract: The surface products have a significant influence on the reactivity of zero-valent iron-based materials. Although the enhancing effect of graphene on the reactivity of nanoscale zero-valent iron (NZVI)/graphene composites have been confirmed, the effect of graphene on the formation of surface products of NZVI is not well understood. In order to assess the effect of graphene on the structural of the outer iron oxide layers of NZVI, the NZVI was pre-oxidized by graphene oxide (ONZVI-GO). Compared with the NZVI oxidized by O2 (ONZVI-O2 ), ONZVI-GO was shown to be effective at NO3 − removal with a high efficiency over a wide range of initial pH values. The results from characterization showed that GO could induce the formation of a tight iron oxide shell with dense spinel structures. The boron introduced during the preparation of NZVI was doped into iron oxides on the surface of ONZVI-GO. The B–O in adsorbed borate was transformed to B–B/B–Fe in the lattice structure of iron oxides, causing the formation of highly electron-deficient Lewis acid sites on the surface of ONZVI-GO, which could effectively gather NO3 − and OH −, leading to the higher efficiency removal of NO3 − than ONZVI-O2 over a wide range of initial pH values. This study provides new insight into the interaction between graphene and the surface species of NZVI. Graphical abstract: Image 1 Highlights: GO can induce the formation of a spinel structure shells on the surface of NZVI. B was doped into surface iron oxide during the interaction between GO and NZVI. The B-doped iron oxide on the surface of NZVI could effectively gather NO3 − and OH − . ONZVI-GO can effectively remove NO3 − over a wide range of initial pH values.